Differential Adaptations of Methicillin-Resistant Staphylococcus aureus to Serial In Vitro Passage in Daptomycin: Evolution of Daptomycin Resistance and Role of Membrane Carotenoid Content and Fluidity - Nagendra N. Mishra; Aileen Rubio; Cynthia C. Nast; Arnold S. Bayer (International Journal of Microbiology)
Previous studies showed serial 20 d in vitro passage of MRSA strain MW2 in sublethal daptomycin (DAP) resulted in diverse perturbations in both cell membrane (CM) and cell wall (CW) characteristics, including increased CM rigidity; increased CW thickness; “gain-in-function” single nucleotide polymorphisms (SNPs) in the mprF locus (i.e., increased synthesis and translocation of lysyl-phosphatidylglycerol (L-PG)); progressive accumulation of SNPs in yyc and rpo locus genes; reduced carotenoid production; cross-resistance to innate host defense peptides. The current study was designed to characterize the reproducibility of these phenotypic and genotypic modifications following in vitro serial passages of the same parental strain. After a second 20d serial in vitro passage of parental MW2, emergence of DAP-R was associated with evolution of several phenotypes closely mirroring previous passage outcomes. However, in contrast to the initial serial passage strain set, we observed (i) only modest increase in L-PG synthesis and no increase in L-PG outer CM translocation; (ii) significantly increased carotenoid synthesis (P<0.05); (iii) a different order of SNP accumulations (mprF≫rpoB≫yycG); (iv) a different cadre and locations of such SNPs. Thus, MRSA strains are not “pre-programmed” to phenotypically and/or genotypically adapt in an identical manner during induction of DAP resistance.